Suara ‘Aisyiyah Magazine: Strengthening Progressive Teaching Islamic Media In Indonesia - Tri Hastuti Nur Rochimah; Hajar Nur Setyowati; Elita Putri Pradipta (Universiti Sains Islam Malaysia, 2025)
Al-i’lam - Journal of Contemporary Islamic Communication and Media, Volume 5 Issue 2 Page (173-184)